Unvalidated efficacy and significant risks hinder clinical use of deep cervical lymphatic-venous anastomosis for Alzheimer’s disease - Zhang, Rui; Liu, Ying Ying; Xia, Xun; Li, Xinjun (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by cognitive decline and the pathological accumulation of amyloid-beta (Aβ) plaques and tau tangles. Recent studies suggest that dysfunction of the cerebral lymphatic clearance system may contribute to the progression of AD. This review critically examines the potential of deep cervical lymphatic-venous anastomosis (LVA) as a treatment for enhancing brain protein clearance and reducing cognitive decline in AD patients. Although animal models indicate that improving lymphatic drainage could facilitate Aβ clearance, clinical evidence is still insufficient. Current studies often have small sample sizes, short follow-up periods, and methodological weaknesses. Despite preliminary reports of cognitive improvements in small-scale clinical trials, the efficacy of LVA remains unproven, making widespread clinical adoption premature. Ethical concerns and technical challenges also pose significant barriers to clinical implementation. Rigorous randomized controlled trials (RCTs) are necessary to assess the long-term safety and efficacy of LVA for treating AD. Furthermore, the establishment of clear ethical and regulatory frameworks is essential before clinical use.